Physical performance analysis of Indonesian sepak takraw: Challenges facing the 2023 Cambodia Sea Games - Aji, Tri; Yudhistira, Dewangga; Paryadi; Pembayu, Septadi Hanif; Dameria, Franciska Dina (UIR Press, 2025)
Background: Physical performance in Sepak Takraw is very important, including speed, agility, and strength. One of the important factors in supporting sepak takraw achievement is physical performance. Physical performance is important to evaluate, but the fact that empirically evaluating the physical performance of Sepak Takraw has not shown a comprehensive evaluation means that a more in-depth evaluation is needed. Research Objectives: This study seeks to assess the physical condition of Indonesian Sepak Takraw athletes throughout the general preparation stage. Methods: Participants in Sepak Takraw were 12 people aged 19-31 years, weighing ± 60-75 kg and ± 164-179 cm tall. The aspects evaluated consist of speed, endurance, agility, power, and muscle endurance. This study's instruments include a 20-meter sprint, a multistage fitness test, sit-ups, a 60-second backup, a shuttle run, and a vertical jump. The data was analysed using quantitative descriptive analysis and the nonparametric Wilcoxon test. Findings and Results: The results of mean speed values obtained in each test are 1 (3.03) and 2 (3.15), endurance test 1 (49.87) and 2 (53.63), situp test 1 (72) and 2 (84), back up test 1 (111) and 2 (119), agility test 1 (5.14) and 2 (5.01), power test 1 (62.83) and 2 (64.17). Regarding the Asymp.sig (2-tailed) value, speed obtained a value of 0.004, endurance 0.004, sit-up 0.010, and agility 0.018 with p < 0.05. Several aspects have seen substantial changes; however, the specific focus should be devoted to the speed aspect, which requires improvement. Conclusion: This evaluation provides information to improve physical performance. Further evaluation is needed to collect more comprehensive data. Future research can build on the findings of the current study, provide deeper insights and more comprehensive strategies to improve the physical performance of Sepak Takraw athletes.